(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Miss. Hyndavi Trylockya Nagumantri, PharmD Scholar, Department of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Kakinada, Andhra Pradesh, India Abstract Ambulatory care pharmacy practice focuses on longitudinal patient care in outpatient settings, emphasizing chronic disease management, preventive services, and care coordination across the healthcare continuum. Chronic disease management implements comprehensive approaches for conditions including diabetes, hypertension, dyslipidemia, and respiratory disorders through collaborative practice agreements, protocol-driven care, and self-management support enhancing clinical outcomes and quality of life. Preventive care services encompass immunization delivery, health screening coordination, medication-related prevention strategies, and lifestyle modification support addressing modifiable risk factors before disease development. Collaborative practice models establish formalized relationships between pharmacists and physicians through scope of practice definitions, communication protocols, and responsibility delineation enabling comprehensive, team-based patient care. Care transition management addresses vulnerable periods between care settings through medication reconciliation, regimen simplification, access assurance, and post-discharge follow-up preventing adverse events and readmissions. Quality measurement methodologies demonstrate impact through standardized metrics addressing process improvement, clinical outcomes, patient satisfaction, and healthcare utilization. This patient-centered approach positions pharmacists as essential primary care team members optimizing medication therapy in longitudinal, community-based settings. Keywords: Chronic Care Management, Preventive Pharmacotherapy, Collaborative Drug Therapy Management, Care Coordination, Quality Improvement VIEW PDF